Leading and managing in the social sector : strategies for advancing human dignity and social justice /: strategies for advancing human dignity and social justice. (2016) - Tirmizi, S. Aqeel; Vogelsang, John D (John Daniel), 1946-; Esty, Katharine C; Davie, Grace; Reeler, Doug; Unsicker, Jeff, 1950-; Poskitt, Adele; Wenzel, Ramon; Hiland, Mary; Rao, Aruna; Kelleher, David, 1944-; (Researcher on gender), Miller, Carol; et al.
No abstract available